Mycale (Aegogropila) magellanica (Porifera: Demospongiae) in the southwestern Atlantic Ocean: Endobiotic fauna and new distributional information - Schejter, Laura (2012)
The composition of endobionts in the sponge Mycale (Aegogropila) magellanica at the shelf-break, near 100 m depth, in the Argentine Sea was studied. We also provide new information on the distribution of M. (A.) magellanica, extending its northern limit to 38o36.02'S and 55o44.68'W, 91 m in the SW Atlantic Ocean. The main Patagonian scallop fishing grounds are located in the shelf-break frontal area of the Argentine Sea. In this area, M. (A.) magellanica plays an important role in providing habitat for at least 23 taxa of small invertebrates, mostly crustaceans (66% to 96% of the total number of individuals). On average, this sponge hosted 348 individuals per litre; Aristias cf. antarcticus (Amphipoda) was the most frequent and abundant species. Other organisms commonly found were the isopod Caecognathia sp., the amphipod Leucothoe cf. spinicarpa, the bivalve Hiatella meridionalis and the ophiuroid Ophiactis asperula. As previously demonstrated for other sponges, our study suggests that M. (A.) magellanica enhances benthic biodiversity, as it shelters a variety of invertebrate species. In areas of soft and flat substrate, erect and sessile epifauna usually acts as an ecosystem engineer, structuring the architecture of the habitat by increasing the sea-bottom complexity. Mass removal of this fauna due to intense trawling activities on Patagonian scallop beds could have devastating effects on local biodiversity.